Perancangan Kampanye Sosial Tentang Pentingnya Pendidikan Karakter untuk Pelajar SMA Sederajat - Ardi Rosyadi; Anin Ditto; Mutia Budhi Utami (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Character education is an effort to apply religious, moral and ethical values to students through science, assisted by parents, teachers and the community which is very important in the formation and development of students' character. In order to create a cultured nation through strengthening religious values, honesty, national spirit, environmental care, social care and responsibility, the government considers it necessary to strengthen character education. Data collection methods were carried out through observation, interviews, literature studies and questionnaires. The data analysis method used is 5W – 1H. The social campaign was carried out through seminars to high schools and vocational schools in Padangpanjang City. The presentation of this social campaign work is presented in the form of an exhibition. An exhibition is an activity to present works that will be communicated and appreciated by the audience. In the exhibition display later, digital works and printed works will be displayed so that the audience can see the media mix that has been designed. From the results of designing a social campaign about the importance of character education for high school students, namely motivating students and female students to implement character education through organizations, culture and religion and improving the quality of Padang Panjang city students in terms of student behavior and attitudes starting from their awareness of the importance of character education ..